Protection of power transformer using microcontroller-based relay - Rafa, A.; Bashi, Senan Mahmood; Mariun, Norman; Wan Hasan, Wan Zuha; Mailah, Nashiren Farzilah (IEEE, 2002)
This paper describes the design and implementation of the micro controller-based system for protecting power transformer. The system includes facilities for discrimination between internal fault current and magnetizing inrush current, differential protection, over current protection, over voltage protection and under voltage protection. In this paper, software and hardware of micro controller based system have been explained and designed. The design implementation and testing of the system are also presented.